Income differences and input-output structure - Harald Fadinger; Christian Ghiglino; Mariya Teteryatnikova (University of Mannheim, Department of Economics, 2015)
We consider a multi-sector general equilibrium model with IO linkages, sector-specific productivities and tax rates. Using tools from network theory, we investigate how the IO structure interacts with productivities and taxes in the determination of aggregate income. We show that aggregate income is a simple function of the first and second moments of the distribution of the IO multipliers, sectoral productivities and sectoral tax rates. We then estimate the parameters of the model to fit their joint empirical distribution. Poor countries have more extreme distributions of IO multipliers than rich economies: there are a few high-multiplier sectors, while most sectors have very low multipliers; by contrast, rich countries have more sectors with intermediate multipliers. Moreover, the correlations of these with productivities and tax rates are positive in poor countries, while being negative in rich ones. The estimated model predicts cross-country income differences extremely well, also out-of-sample. Finally, we perform a number of counterfactuals and compute optimal tax rates.
urn:nbn:de:bsz:180-madoc-396276
Keywords: O11; O14; O47; C67; D85; 330; input-output structure; networks; productivity; cross-country income differences